Studies on Removal of Fipronil (FP) Pesticide From Its Aqueous Solution By A Low-Cost Adsorbent - Mehta, Tanishka (My University, 2019)
The current investigation was carried out to figure out the performance of Cu-X as an adsorbent for the elimination of FP pesticide from wastewater. 13X zeolite were modified with copper nitrate solution & modified zeolite was used for adsorption studies. To prepare the adsorbent, 13X zeolite was refluxed with ammonium nitrate solution at 90◦ C for 6 hours, for three times and calcined for 3 hours at 350◦C in between to form HX. After final calcinations, it was refluxed with copper nitrate solution at a temperature of 90◦C for 72 hours. Adsorption experiments were carried out over copper modified zeolite (Cu-X) as adsorbent varying different parameters such as pH of the solution, stirring speed, dose of adsorbent, initial concentration of the solution. The modified adsorbent Cu-X was used to remove Fipronil pesticides from its aqueous solution. Experimentation was performed at least twice a time and the mean values were reported to assure the accuracy of the results. FP pesticide was removed from its aqueous solution increases with increase in adsorbent dose and contact time, the best % removal of Fipronil was obtained to be 92.3%. At optimum pH 3, 84.2% removal of Fipronil is obtained. The elimination of Fipronil decreases with the increase in initial conc. of pesticide. Effect of temperature on Fipronil elimination was also studied. At 25◦C, the maximum percent removal reported being 92%. Also, the maximum removal is 92.3% at an optimum stirring speed of 200rpm. In the data of experimentation, the Freundlich isotherm fitted properly whereas the process of adsorption obeyed second-order kinetic model. Thermodynamics study was also carried out.
Keywords: EDCs; Fipronil; Adsorption; Removal; Modified Zeolite